The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acs.energyfuels.7b00314
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Miscible Thickened Natural Gas Injection for Enhanced Oil Recovery

Abstract: Hydrocarbon-miscible gas flooding typically involves injection of an associated gas (AG) mixture containing mainly methane (CH 4 ) enriched with light hydrocarbon fractions and possibly acid gases. The AG mixture has been recognized as an excellent candidate for miscible gas injection (MGI). However, in general, the viscosity of the AG at reservoir conditions is significantly lower than that of crude oil leading to an unfavorable mobility ratio and low volumetric sweep efficiency during flooding. This study as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…The severe cases of unfavorable mobility ratios may lead to early water (chemical) or gas breakthrough to production wells (Agi et al 2018;Al Hinai 2017). High reservoir conditions such as high temperature in most cases contribute to these aforementioned factors, because the viscosity of the injected fluids decreases tremendously with temperature causing fingering to oil bank.…”
Section: Introductionmentioning
confidence: 99%
“…The severe cases of unfavorable mobility ratios may lead to early water (chemical) or gas breakthrough to production wells (Agi et al 2018;Al Hinai 2017). High reservoir conditions such as high temperature in most cases contribute to these aforementioned factors, because the viscosity of the injected fluids decreases tremendously with temperature causing fingering to oil bank.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the miscible PDMS‐CO 2 thickener scenario is considered at the beginning of the reservoir life, it can be more effective than other scenarios. [ 16 ] In addition, the JBN technique was used to obtain the gas/oil relative permeability. The PDMS thickener provides the miscible conditions during the coreflooding scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [ 17 ] illustrated that the small molecule thickeners of hydroxy aluminium soap and tri‐alkyl‐tin fluoride significantly enhances the viscosity of propane and butane 6‐10‐fold compared to the cross‐linked phosphate ester mixtures. Alhinai et al [ 16 ] used the poly 1‐decene (P‐1‐D), PDMS, and (polymethylhydrosiloxane) PMHS as small molecule thickeners for miscible thickened natural gas flooding. Also, a hydrocarbon gas mixture containing methane (60%), ethane (9%), propane (6%), and carbon dioxide (25%) was considered as an injection gas at reservoir conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies, reported that for low/high molecular weight polymers, a concentration of 1.5-7 wt% is required to thicken CO 2 albeit at very high pressure [6]. In recent studies, [16,17] P-1-D has been found to have sufficient solubility in both CO 2 and associated gas (AG) mixtures (at temperatures above 358 K and pressures of 50-55 MPa) to considerably increase gas viscosity. The viscosity enhancement of P-1-D in an AG mixture (25 mol% CO 2 ) and CO 2 was measured in a capillary viscometer at different pressures (50-55 MPa), 377 K, and varying P-1-D concentrations (1.5-9 wt%).…”
Section: Direct Carbon Dioxide Thickeners 21 Polymeric Thickenersmentioning
confidence: 99%